Handgrip strength and ball velocity of young male and female handball players - Tsakalou, L.; Kotsampoukidou, Z.; Papa, M.; Zaparidis, I. (Journal of Physical Education and Sport, 2015)
The aim of the current study was to compare the performance of handgrip strength and ball velocity between boys and girls of two different age groups (12 and 13 years) and consequently investigate the correlation between these two parameters. The sample consisted of 121 adolescent handball players (74 males, 47 females), divided into four groups depending on the age and sex: boys and girls 12- and 13-years old. Stature, body mass, palm width, palm length, ball velocity and handgrip strength were measured. In the 12 years age group, male handball players had significantly longer palm length and performed significantly better than female ones in ball velocity. In the 13-years age group, male handball players were significantly taller, heavier, had longer palm width and palm length, and performed significantly better than female ones in ball velocity and handgrip strength. In the 13-years age group, maximal handgrip strength showed more powerful correlations to those of the 12 year olds, in all the examined variables. After controlling for body mass, the relationship between grip strength and body height was not significant, however ball velocity and hand length were still correlated to grip strength.